Capillary versus venous bedside blood glucose estimations. Issue 3 (25th February 2005) - Boyd, R; Leigh, B; Stuart, P
Abstract : Objectives: To determine the mean difference and correlation between capillary and venous bedside glucose estimation in comparison to laboratory blood glucose analysis in emergency department (ED) patients. Methods: Blood glucose levels were synchronously analysed using a bedside blood glucometer on capillary and venous derived samples from consenting ED patients aged >12 years. The venous sample was sent for comparative testing using a laboratory based multichannel analyser. Mean difference and correlation coefficients were determined. Results: A total of 20 subjects (aged 13–88 years) were enrolled, with 100% data capture. The mean laboratory glucose was 7.075 mmol/l. The mean capillary blood glucose was 7.66 mmol/l (mean difference compared with mean laboratory glucose 0.58 mmol/l; 95% confidence interval 0.3 to 0.9). The mean venous derived blood glucometer glucose was 7.99 mmol/l (mean difference compared with mean laboratory glucose 0.91 mmol/l; 95% CI 0.6 to 1.2). The correlation coefficient for the laboratory blood glucose versus the capillary blood glucometer glucose was 0.97 mmol/l (p<0.001). The correlation coefficient for the laboratory blood glucose and the venous blood glucometer glucose was 0.96 (p<0.001). Variation occurred between the glucometer and the laboratory blood glucose results. Conclusions: There is a small but significant difference in the blood glucose results analysed on a bedside glucometer when the samples are taken from capillary or venous sources. Although good correlation is the norm between venous and capillary derived samples, caution must be exercised in accepting the results as equivalent or using either as substitutes for a laboratory blood glucose result.